The interaction of grammatically distinct agreement dependencies in predictive processing. Issue 9 (1st November 2021) - Stone, Kate; Veríssimo, João; Schad, Daniel J.; Oltrogge, Elise; Vasishth, Shravan; Lago, Sol
ABSTRACT: Previous research has found that comprehenders sometimes predict information that is grammatically unlicensed by sentence constraints. An open question is why such grammatically unlicensed predictions occur. We examined the possibility that unlicensed predictions arise in situations of information conflict, for instance when comprehenders try to predict upcoming words while simultaneously building dependencies with previously encountered elements in memory. German possessive pronouns are a good testing ground for this hypothesis because they encode two grammatically distinct agreement dependencies: a retrospective one between the possessive and its previously mentioned referent, and a prospective one between the possessive and its following nominal head. In two visual world eye-tracking experiments, we estimated the onset of predictive effects in participants' fixations. The results showed that the retrospective dependency affected resolution of the prospective dependency by shifting the onset of predictive effects. We attribute this effect to an interaction between predictive and memory retrieval processes.